2016
DOI: 10.1080/17425247.2017.1260119
|View full text |Cite
|
Sign up to set email alerts
|

Fractional laser-assisted topical delivery leads to enhanced, accelerated and deeper cutaneous 5-fluorouracil uptake

Abstract: AFXL offers laser-channel depth-dependent, enhanced and accelerated 5-FU uptake, with increased deposition in deep skin layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 52 publications
9
56
0
Order By: Relevance
“…Previous studies have shown that laser-assisted drug delivery depends on laser settings and drug characteristics such as its LogP (low for hydrophilic drugs and high for hydrophobic drugs). In the case of the hydrophilic drug 5-fluorouracil (LogP À0.58), AFL exposure increases uptake after 24 hours by 16-82 fold compared to intact skin and the effect is dependent on laser pulse energy [12]. On the other hand, the uptake of ingenol mebutate, a hydrophobic drug (LogP 2.49), was shown to increase only 1.6-3.9 fold in dermis after 21 hours depending on laser density but independent of laser pulse energy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that laser-assisted drug delivery depends on laser settings and drug characteristics such as its LogP (low for hydrophilic drugs and high for hydrophobic drugs). In the case of the hydrophilic drug 5-fluorouracil (LogP À0.58), AFL exposure increases uptake after 24 hours by 16-82 fold compared to intact skin and the effect is dependent on laser pulse energy [12]. On the other hand, the uptake of ingenol mebutate, a hydrophobic drug (LogP 2.49), was shown to increase only 1.6-3.9 fold in dermis after 21 hours depending on laser density but independent of laser pulse energy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques to enhance TDD include curettage, dermabrasion, iontophoresis, pressure waves, vacuum, and radiofrequency. Using these modalities, a myriad of medications have been successfully delivered transdermally, including triamcinolone, 5-aminolevulinic acid (5-ALA), 5-fluorouracil (5-FU), and methotrexate [5][6][7][8][9][10][11].…”
Section: Transdermal Drug Delivery (Tdd)mentioning
confidence: 99%
“…1,2 In recent years, LADD has been reported to enhance uptake of several drugs. [4][5][6] The use of ablative fractional laser drug delivery of BTX was previously reported for treatment of periorbital wrinkles, 7 but this is the first trial of LADD for palmar hyperhidrosis to be reported in the literature.…”
mentioning
confidence: 96%